Pengaruh Merger Dan Konglomerasi Terhadap Penilaian Industri - Muhammad Yasin; Danendra Bramantyo; Jasmine Damayanti; M. Ibrahim Baihaqi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Merge is the origin of the word merger that we currently know, which comes from a word which means in Indonesian, namely to combine or fuse. According to the definition of the Encyclopedia of Banking and Finance, merger itself is defined as combining two or more entities or companies, where the large one takes the small one and then the one who continues the business usually uses the same name. Meanwhile, according to the republican government, a merger is defined as a legal act carried out by two or more companies to merge with another existing company and then the merging companies are dissolved.